SHEEHAN’S SYNDROME: CURRENT INSIGHTS INTO PATHOPHYSIOLOGY, CLINICAL MANIFESTATIONS, DIAGNOSTIC CHALLENGES AND MANAGEMENT STRATEGIES - Natalia Musialik; Maciej Magiera; Barbara Starosta; Monika Pelczar; Bartosz Brzychcy; Karolina Brzychcy; Karolina Paks; Zuzanna Gajda; Ewa Jench (International Journal of Innovative Technologies in Social Science, 2025)
Aims: Sheehan’s Syndrome (SS), also known as postpartum hypopituitarism, is a rare and potentially life-threatening endocrine disorder caused by ischemic necrosis of the pituitary gland due to massive postpartum hemorrhage and hypovolemic shock. The aim of this article is to present a comprehensive and up-to-date overview of the current understanding of Sheehan’s syndrome, including its pathophysiology, epidemiology, clinical presentation, diagnostic challenges, and therapeutic approaches.Methods: A narrative review of the literature was conducted using the PubMed, Oxford Academic, Google Scholar, and Embase databases. The analysis included original research articles, systematic reviews, and clinical guidelines published in English over recent years.Results: Sheehan’s syndrome remains an underdiagnosed condition due to its highly variable and often delayed clinical presentation. Symptoms may appear months to years after the inciting obstetric event, which hinders timely diagnosis. The most common manifestations include failure to lactate, amenorrhea, fatigue, hypotension, and features of secondary hypothyroidism or adrenal insufficiency. MRI typically reveals an empty sella or pituitary atrophy. Hormonal testing confirms multiple anterior pituitary hormone deficiencies. The condition is still most prevalent in regions with inadequate obstetric care.Conclusions: Early recognition of Sheehan’s syndrome, based on detailed obstetric history and characteristic clinical and laboratory findings, is essential to prevent severe complications and reduce diagnostic delays. Increased awareness among primary care physicians and perinatal care providers is crucial. Timely initiation of appropriate hormone replacement therapy can significantly improve patient outcomes and quality of life.